2017
DOI: 10.1055/s-0036-1597990
|View full text |Cite
|
Sign up to set email alerts
|

Video-Assisted Laser Resection of Lung Metastases—Feasibility of a New Surgical Technique

Abstract: Our pilot study describes our initial experience to do a laser resection of lung metastases under video-assisted thoracoscopic control via a minithoracotomy. With this approach, if needed, mediastinal lymphadenectomy is also possible. In this study, 15 patients (11 men and 4 women, mean age: 60 years) with resectable lung metastases of different solid primary tumors (colorectal cancer in seven patients, melanoma in three patients, renal cell carcinoma in two patients, and one each with oropharyngeal cancer, br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Even more centrally located lung metastases can be removed with precision, omitting the need for anatomical resection. Video-assisted resection via mini-thoracotomy using a focusing handpiece of the kind employed in open surgery is feasible, as we were able to demonstrate in a small study (17). For this less invasive application however, these commercially available handpieces are frequently too short and correct alignment with the lung parenchyma inside the thoracic cavity may be difficult.…”
Section: Introductionmentioning
confidence: 76%
“…Even more centrally located lung metastases can be removed with precision, omitting the need for anatomical resection. Video-assisted resection via mini-thoracotomy using a focusing handpiece of the kind employed in open surgery is feasible, as we were able to demonstrate in a small study (17). For this less invasive application however, these commercially available handpieces are frequently too short and correct alignment with the lung parenchyma inside the thoracic cavity may be difficult.…”
Section: Introductionmentioning
confidence: 76%
“…Equal survival could previously be shown after VATS surgery compared to thoracotomy in several cases ( 12), yet extent and technique of surgery required for detecting all nodules remain avidly discussed (12)(13)(14)(15)(16). A combined approach using a minithoracotomy that allows thorough palpation of the lung and performing the resections under video-assisted thoracoscopic control has also been proposed (17). However randomized controlled trials are still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Lasers can be used to excise more metastases while achieving an equivalent long-term survival rate and enabling re-operations when necessary [ 18 ]. Some previous studies have even demonstrated the superiority of laser ablation compared with standard surgical procedures in terms of the success of radical resection, patient survival rates, the simplicity of video-guided laser procedures during minithoracotomy, and the possibility of intra-operative lung palpation [ 19 , 20 ]. In summary, laser use in lung surgery is highly promising due to the fact of its prevention of hemorrhaging during and post-surgery, its preservation of healthy lung tissue as well as the possibility it provides of removing cavernous lesions in sites that were previously inaccessible surgically [ 21 ].…”
Section: Introductionmentioning
confidence: 99%